The influence of emotional intelligence and learning style on student's academic achievement / Dr. Kuldip Singh ... [et al.] - Singh, Kuldip; Maghar Singh, Baljinder Singh; Ali, Jati Kasuma (2008)
This study explores the influence of emotional intelligence and learning styles on academic achievement of University Technology Mara Sarawak students. A sample size of 500 students at the diploma and bachelor level was selected for the study. The total number of usable questionnaires returned was 389 which gave a response rate of 78 %. Emotional Intelligence Questionnaire (EIQ), an adapted version of the Self-Report Emotional Intelligence Test (SREIT) developed by Schutte et.al (1998), was used in this study to measure emotional intelligence. The learning styles were measured using Learning Style Questionnaire (LSQ) which comprised adapted items from the 'VARK Learning Styles Inventory' developed by Neil Fleming (1987).